Observation of the spread of slow deformation in Greece following the breakup of the slab. Issue 20 (29th October 2014) - Durand, Virginie; Bouchon, Michel; Floyd, Michael A.; Theodulidis, Nikos; Marsan, David; Karabulut, Hayrullah; Schmittbuhl, Jean
Abstract Over the past two decades, geophysical observations have shown that earthquakes can trigger other earthquakes, raising the possibility that earthquake interaction plays an important role in the earth's deformation. We analyze here a "storm" of earthquakes in Greece and show that their interaction provides remarkable insight into the mechanics of one of the fastest deforming continental region in the world. A rupture of the African slab initiates a cascade of large earthquakes and a long episode of slow slip marking the downward plunge of the slab, the concomitant rollback of the subduction, and the subsequent detachment of southern Greece from the Eurasian plate. Intense crustal deformation, indicative of the resulting plate stretching, follows. This slow deformation which spreads in a few months over more than 500 km lasts ~3 years and triggers earthquakes. The observations also show that the retreat of the African subduction is the motor of the Aegean deformation.